Simulação da propagação de cheias em canais urbanos: análise da implantação de meandros controlados - Souza, Sandro Marcello de (2016)
The objective of this work was to simulate urban flood propagation situations in micro basin Stream Jataí in Uberlândia (Minas Gerais). This study was done through simulation of the implementation of controlled meanders in the pipeline of that course and its consequences for the flow in exutório, shear stress, flow speed, blade height of water and maximum flow. For both proceeded to the geomorphological study of the basin, its sources and contributions made by implanted stormwater networks as well as the influence of the occupation of the area under socioeconomic point of view according to recent legislation classification and territorial characterization. The simulation included changing the profile and path of the channel, as well as its sinuous. Comparisons between multiple levels of service; of building material (concrete) bed and "naturalized". In this way, you can test and evaluate the influence of these technical possibilities on parameters such as flow, shear stress and flow height, among others. In the search for new ways to mitigate the problem of urban flooding, slowing the flow and reducing the destructive effects so common to these situations.